Theory of stages applied to the studies of motor development: a revision - Inara Marques (Revista da Educação Física)
Theory of stages applied to motor development was based on development psychology, proposed by Piaget. The idea was that the cognitive behavior was undergoing qualitative changes called stages. And it was that idea which provided the basis for building a theory of stages for motor behaviour. Since then, the goal of the professional who works with motor development has been to try to explain the process of acquisition of fundamental movements through a hierarchical sequence of stages, identified since the first movement manifestation until its execution in a mature way. This article, however, aims not at confirming the theory of stages as adequate, but at carrying out an explanation about such theory applied to the studies of motor development, considering its principal characteristics as well a discussion of such content in face of new trends.